Work motivation, job satisfaction, work-family balance, and job commitment of library personnel in Universities in North-Central Nigeria - Popoola, Sunday Olanrewaju; Fagbola, Olaronke O. (The Journal of academic librarianship, 2023)
Increasingly, organizations are facing turbulent and competitive times. Hence, the need for universities to capitalize on the robustness and diversity of their employees to maximize their success by attracting and developing an engaged, healthy, and high-performing workforce through the provision of stimulating work environments that will promote work-family balance, work motivation, job satisfaction and overall job commitment. This study was designed to investigate the effects of work motivation, job satisfaction, and work-family balance on job commitment as well as work motivation and work-family balance as they affect job satisfaction of library personnel in universities in North-central Nigeria. The total enumeration technique was used to cover all the 926 library personnel in the universities in North-central Nigeria. The validated questionnaire was used to collect data on 926 library personnel out of which 842 responded. The response rate achieved was 91 %. The study found that work-family balance, work motivation and job satisfaction had significant effect on the job commitment of the respondents. Job satisfaction has the most significant effect (41 %) on job commitment. It is therefore, recommended that university administrators, library managers and most especially policy makers in the education sector should give adequate attention to work-family balance, work motivation, and job satisfaction when planning to improve job commitment of their employees. In addition, they should consider work motivation and work-family balance to improve job satisfaction of the library employees. •Work-family balance, work motivation and job satisfaction had significant effect on the job commitment of the respondents.•Job satisfaction has the most significant effect on job commitment.•Work-family balance, work motivation and job satisfaction jointly affect job commitment of the respondents.•Work motivation and work-family balance jointly affect job satisfaction of the respondents